2009
DOI: 10.1086/599213
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Vaginal Bacterial Flora and Other Risk Factors for Vulvovaginal Candidiasis

Abstract: Background: It has been suggested that vaginal lactobacilli may reduce the risk of vulvovaginal candidiasis (VVC), but supporting data are limited. Our objective was to determine the relationship between vaginal bacterial flora and VVC. Methods: We conducted a prospective cohort analysis among 151 Kenyan sex workers. At monthly follow-up, VVC was defined as the presence of yeast buds, pseudohyphae, or both on vaginal wet preparation or KOH preparation. Generalized estimating equations were used to identify c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
4
58
0
5
Order By: Relevance
“…In particular, colonization of the vagina implies sharing of this mucosal environment with lactic acid-producing Lactobacillus spp., which are the main colonizing flora. Interestingly, while older studies have suggested a protective effect of lactobacilli on vaginal colonization with fungi (57), more recent research has revealed that Lactobacillus colonization of the vagina is a strong risk for vulvovaginal candidiasis (58). Our study provides the first evidence for the mechanisms by which lactate supplied by the Lactobacillus vaginal flora could contribute to this process.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, colonization of the vagina implies sharing of this mucosal environment with lactic acid-producing Lactobacillus spp., which are the main colonizing flora. Interestingly, while older studies have suggested a protective effect of lactobacilli on vaginal colonization with fungi (57), more recent research has revealed that Lactobacillus colonization of the vagina is a strong risk for vulvovaginal candidiasis (58). Our study provides the first evidence for the mechanisms by which lactate supplied by the Lactobacillus vaginal flora could contribute to this process.…”
Section: Discussionmentioning
confidence: 53%
“…Similar to the oral cavity, C. albicans is a resident of the normal vaginal microbiota and the leading causative agent of vulvovaginal candidiasis (VVC) (14,(130)(131)(132)(133)(134)(135) (Fig. 2F).…”
Section: Non-cd4mentioning
confidence: 99%
“…116 Recently, however, one group has posited that their findings are more consistent with Lactobacillus being associated with greater risk for vulvovaginal candidiasis. 117 By elucidating the mechanism by which lactic acid suppresses immune responses to C. albicans, Ene et al 46 have supplied evidence for this claim.…”
Section: 100mentioning
confidence: 99%